SOCIAL MANAGEMENT STRATEGIES IN COUNTERING RADICALISM AND EXTREMISM: EDUCATIONAL, COMMUNITY, AND POLICY PERSPECTIVES - Prisca Diantra Sampe; Izak Jakobis Makulua (Adisam Publisher, 2026)
Radicalism and extremism have become increasingly complex global challenges that threaten social cohesion, democratic stability, and community resilience in contemporary societies. The rapid development of digital communication, ideological polarization, and transnational extremist networks has intensified the spread of radical narratives across educational, social, and political environments. This study aims to analyze social management strategies for countering radicalism and extremism from educational, community, and policy perspectives using a literature review. The research employed a qualitative library research method, examining recent scholarly publications, policy reports, and peer-reviewed international journal articles on social resilience, counter-radicalization, educational interventions, community collaboration, and preventive governance. The findings indicate that preventive and collaborative social management approaches are more effective and sustainable than purely security-oriented strategies. Educational institutions play significant roles in promoting critical thinking, multicultural awareness, digital literacy, and moderate values to prevent ideological vulnerability among young people. Community collaboration strengthens social trust, intercultural dialogue, and participatory resilience, while inclusive public policies provide structural support for sustainable prevention efforts. The study also reveals that integrated social management frameworks are essential because radicalization is influenced by interconnected cognitive, emotional, social, and structural factors. Furthermore, the literature highlights several challenges, including institutional fragmentation, online radicalization, socioeconomic inequality, and political polarization, which continue to hinder prevention efforts. This study contributes to theory by integrating educational, community, and policy dimensions into a holistic framework to strengthen social resilience against radicalism and extremism. Practically, the study emphasizes the importance of cross-sectoral collaboration and preventive governance in developing adaptive and inclusive strategies to maintain social harmony and democratic sustainability in the digital era.